PENGARUH RASIO EFISIENSI, RISIKO OPERASI DAN LIKUIDITAS TERHADAP PROFITABILITAS PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2018 - Buulolo, Elisabet Mariani; Zalmi, Fony Yurika; Sihite, Ayu; Daulay, Nadia Nurhaliza; Sakuntala, D (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
This study aims to determine and to analyze the effect of the efficiency ratio, operation risk and liquidity against profitability in Textile and Garment Sub Sector Companies listed on the Indonesia Stock Exchange for the period 2012-2018. The research method used in this research is quantitative research methods, the type of research is quantitative descriptive. The population in this study were all companies in the Textile and Garment Sub-Sector as many as 17 companies with purposive sampling techniques obtained by 6 companies the data analysis method used in this study is the method of multiple linear regression and the classical assumption test. The results of this study indicate that simultaneously efficiency ratio, liquidity operational risk has a significant effect on profitability in the Textile and Garment sub-sector companies listed on the Indonesia Stock Exchange for the period 2012-2018 with the results of Fcount = 4.586> Ftable = 2.85. Partially, the efficiency and operational risk ratios have no significant effect on profitability while liquidity has a positive and significant effect on profitability with a tcount = 3.382> ttable = 2.02619 with a significant value of 0.002 <0.05.